OPTIMASI PRODUKSI XILANASE OLEH B.subtilis AQ1 MENGGUNAKAN RESPONSE SURFACE METHODOLOGY - PUTRA, AIDHYA IRHASH (Sainstek : Jurnal Sains dan Teknologi, 2012)
Xylanase is an important enzyme for xylan degradation into xylan derivative compounds such as xylose, xylobiose, xylotriose and other oligoxylan. Xylan derivatives can be bioconverted into bioenergy (ethanol), food ingredients as well as pharmaceutical or nutraceutical goods. Some bacteria have been reported to produce xylanases using defferent kinds of agricultural wastes as a substrate. The objective of this experiment was to optimize the concentration of corn cobs as a carbon source and liquid tofu waste as nitrogen source on xylanase production by Bacillus subtilis AQ-1. A 22 central composite experimental design was performed to optimize the corn cobs and liquid tofu waste concentration. A second order quadratic model and a response surface method showed that the optimum condition for xylanase production was 1.1 % (w/v) corn cobs and 0.00198 % (v/v) total N of liquid tofu waste with the highest xylanase production of 122.99 U/ml.Key words: bacillus subtilis AQ-1, xylanase, corn cob, liquid tofu waste